2016
DOI: 10.3389/fmicb.2016.00549
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Molecular Characterization, and Antibiotic Susceptibility of Vibrio parahaemolyticus from Ready-to-Eat Foods in China

Abstract: Vibrio parahaemolyticus is the leading cause of foodborne outbreaks, particularly outbreaks associated with consumption of fish and shellfish, and represents a major threat to human health worldwide. This bacterium harbors two main virulence factors: the thermostable direct hemolysin (TDH) and TDH-related hemolysin (TRH). Additionally, various serotypes have been identified. The extensive use of antibiotics is a contributing factor to the increasing incidence of antimicrobial-resistant V. parahaemolyticus. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
38
3
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 54 publications
6
38
3
1
Order By: Relevance
“…The antibiotic profiles of the isolates characterized in this study did not coincide with the clustering of ERIC and PFGE. This is consistent with a previous study on antibiotic susceptibility of V. parahaemolyticus from ready-to-eat foods in China (Xie et al, 2016).…”
Section: Discussionsupporting
confidence: 93%
“…The antibiotic profiles of the isolates characterized in this study did not coincide with the clustering of ERIC and PFGE. This is consistent with a previous study on antibiotic susceptibility of V. parahaemolyticus from ready-to-eat foods in China (Xie et al, 2016).…”
Section: Discussionsupporting
confidence: 93%
“…Currently, to rapidly and effectively control and terminate the proliferation of pathogenic Vibrio sp., the prophylactic and therapeutic use of antibiotics has been widely employed in hatcheries, the transportation and sales chain; this is despite urgent concerns regarding the development and dispersal of multiple antibiotic-resistance in the pathogen community. Indeed, microbiological risk assessments revealed that both aquatic products and ready-to-eat foods in China can be contaminated by antimicrobial-resistant V. parahaemolyticus, with the highest resistance rates observed against streptomycin (Xie et al, 2015(Xie et al, , 2016(Xie et al, , 2017Xu et al, 2016). Evidently, as antibiotic-resistant strains cause treatment failure, inducing the violent death of these bacteria is a challenge.…”
Section: Introductionmentioning
confidence: 99%
“…The causative agent of AHPND in shrimp is Vibrio parahaemolyticus; a gram-negative rod shaped bacterium mainly inhabitant in marine and estuarine environment (3). V. parahaemolyticus lives in warm estuarine and marine environments and distributes throughout the world (7). AHPND causing V. parahaemolyticus possesses ~69 kb plasmid encoding toxin genes pirA and pirB (3,8) which are similar to Photorhabdus insect-related (pir) toxin (9) which is one of the major causal factors reported.…”
Section: Introductionmentioning
confidence: 99%